2009
DOI: 10.1007/s00404-009-1297-4
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between bone mineral density, bone turnover markers and homocysteine, folate and vitamin B12 levels in postmenopausal women

Abstract: Our data showed that vitamin B12, folate and Hcy levels were not related with BMD in postmenopausal women. We think that one of the underlying mechanisms of increased Hcy levels and osteoporosis may be a mechanistic link which cannot detected by BMD or biochemical markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 24 publications
1
31
1
Order By: Relevance
“…Herrman et al [21] failed to find association between Hcy and BMD similar to previous study in the group of postmenopausal Iranian women [17]. Similar to our results recent study of Haliloglu et al [20] showed that vitamin B 12 , folate and Hcy levels were not related with BMD [20].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Herrman et al [21] failed to find association between Hcy and BMD similar to previous study in the group of postmenopausal Iranian women [17]. Similar to our results recent study of Haliloglu et al [20] showed that vitamin B 12 , folate and Hcy levels were not related with BMD [20].…”
Section: Discussionsupporting
confidence: 88%
“…Contrary to all mentioned studies, recent research reported no association between folate, vitamin B 12 , Hcy levels and BMD [20], while Herrmann et al [21] reported no significant relations between Hcy and BMD measured at different sites [21].…”
Section: Introductionmentioning
confidence: 94%
“…Eight studies [18, 21, 22, 24–26, 28, 29] were conducted in Turkey, 4 [6, 15, 31, 34] were from Italy, and the others were from India [32], UK [30], Morocco [27], Iran [23], and China [33], respectively. The study size was relatively small with the number of cases ranging from 22 to 110 and the number of controls from 15 to 110.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that vitamin B12 and folate are correlated with BMD in postmenopausal women and the possibility of involvement of a mechanistic link was suggested [37]. …”
Section: Discussionmentioning
confidence: 99%